(3GdebUO GdLdjd aj Yde GdNdjds - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s
(3ChdgG (B:s
(3hHYO Ef YQhV GdTYQ bO UYHJ fKQkG aNP fXegG JLOg s
(3BNQgG (B:s
(3hJVejf HjJ Cf jfGW HZjQg jhVM eYfGg JeJ GdbUjOI HMeO Gddg hefg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3GfXQ bUjOI ai Yde GdYQhV JMJ Qbe (B25 (3YQhV hbhGais
(3fSNI QGHYI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdYQhV hGdbhGais